The diagnostic value of ultrasonography in detection of different types of thyroid nodules - Ahmed Youssef; Mohamed Hesham Abd-Elmonem; Rania Ahmed Mohamed Ghazy; Mohamed Mahmoud El Shafei; Mohamed Zahran (The Egyptian Journal of Otolaryngology, 2020)
Abstract Background This article discusses the importance of high frequency ultrasonography in detection of different types of thyroid nodules considering only the histopathological examination of the surgical specimens as the final diagnosis. We studied 50 patients referred to ENT clinic with a thyroid nodule. Ultrasonography and ultrasound-guided fine-needle aspiration biopsy were done to all the patients. Thyroid surgery was done according to FNAB results. Result From 50 thyroid specimens, the US could predict the malignancy in 18 specimens. By histopathology, only 16 specimens were malignant, and 34 were benign thyroid disease. The sensitivity, specificity, and accuracy of US were 100%, 94.12%, and 96% respectively. The most suspicious ultrasongraphic feature was microcalcification followed by taller than wider (T ˃ W). Conclusion High frequency ultrasound is a very important tool to predict the malignant possibility during thyroid nodule evaluation.